Penentuan Indeks Kualitas Air Sungai Bedadung Kabupaten Jember Menggunakan Metode IP dan NSF-WQI - Elida Novita; Jefri Wahyudi Firmansyah; Hendra Andiananta Pradana (Jurnal Ilmu Lingkungan, 2023)
Good water quality is a support in the sustainability of living things. Monitoring the status of water needs to be done to determine the quality of water and make a basic reference in making decisions for Water Quality Management. The research is aimed to assess the water quality status of the Bedadung River in Rambipuji, Balung and Puger districts using IP and NSF-WQI methods. Sampling was carried out in August 2021 at 4 points using primary data. The results showed that the parameters exceeded the quality standard, namely total phosphate, TSS and fecal coliform. Pollution index calculation shows Bedadung waters classified as Grade 3 quality standard. Based on the NSF - WQI method, the status of Bedadung River is classified as medium category